Distribution of Glyphosate-Resistance in Echinochloa crus-galli Across Agriculture Areas in the Iberian Peninsula - Vázquez-García, José G.; Rojano-Delgado, Antonia M.; Alcántara-de la Cruz, Ricardo; Torra, Joel; Dellaferrera, Ignacio; Portugal, João; De Prado, Rafael (Frontiers in Plant Science, 2021)
The levels of resistance to glyphosate of 13 barnyard grass (Echinochloa crus-galli) populations harvested across different agriculture areas in the Southern Iberian Peninsula were determined in greenhouse and laboratory experiments. Shikimate accumulation fast screening separated the populations regarding resistance to glyphosate: susceptible (S) E2, E3, E4, and E6 and resistant (R) E1, E5, E7, E8, E9, E10, E11, E12, and E13. However, resistance factor (GR50 E1–E13/GR50 E6) values separated these populations into three groups: (S) E2, E3, E4, and E6, (R) E1, E5, E7, E8, and E9, and very resistant (VR) E10, E11, E12, and E13. 14C-glyphosate assays performed on two S populations (E2 and E6) showed greater absorption and translocation than those found for R (E7 and E9) and VR (E10 and E12) populations. No previous population metabolized glyphosate to amino methyl phosphonic acid (AMPA) and glyoxylate, except for the E10 population that metabolized 51% to non-toxic products. The VR populations showed two times more 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) activity without herbicide than the rest, while the inhibition of the EPSPS activity by 50% (I50) required much higher glyphosate in R and VR populations than in S populations. These results indicated that different target-site and non-target-site resistance mechanisms were implicated in the resistance to glyphosate in E. crus-galli. Our results conclude that resistance is independent of climate, type of crop, and geographic region and that the level of glyphosate resistance was mainly due to the selection pressure made by the herbicide on the different populations of E. crus-galli studied.